Identification of novel Jingmen tick virus from parasitic ticks fed on a giant panda and goats in Sichuan Province, southwestern China - Huang, Lin; Liu, Shunshuai; Chen, Lu; Wang, Fei; Ye, Ping; Xia, Luoyuan; Jiang, Baogui; Tang, Hao; Zhang, Qingyu; Ruan, Xiangdong; Chen, Weijun; Jiang, Jiafu (Frontiers in Microbiology, 2023)
Tick-borne viruses (TBVs) pose important risk to the health of humans and other vertebrates. Jingmen tick virus (JMTV) is a multisegmented flavi-like virus related to unsegmented flaviviruses, which was first discovered in Rhipicephalus microplus ticks collected from Jingmen city of Hubei Province in China in 2011, and has been confirmed to be associated with human diseases. Afterwards, some other segmented flavi-like viruses were reported in arthropods, insects and vertebrates, which were tentatively named as “Jingmenvirus group”. Nevertheless, there are no studies on JMTV in Sichuan province. Here, a total of 19 ticks were collected in Sichuan Province, including 17 ticks fed on giant pandas and goats as well as two host-seeking ticks. Complete RNA genomes of four tick samples (PC-13, PC-16, PC-18 and PC-19) were attained through high-throughput sequencing, sharing high similarity with JMTV. Phylogenetic analysis indicated that the RNA viruses recovered from 4 tick samples was a novel JMTV-like virus, referred to it as Sichuan tick virus. In summary, further researches are needed to elucidate the pathogenicity of Sichuan tick virus to human and animals and its epidemiological characteristics in nature.